Syntheses and Characterization of Silica Nanoparticles Grafted with Selected Heterocyclic Derivatives - Shafqat, Syed Salman. (unimas, 2016)
Sol-gel process has been used to synthesize amino functionalized silica nanoparticles by using gelator precursor tetraethylorthosilicate (TEOS) as well as tetramethoxyorthosilicate (TMEOS) and surface modifier, 3-Aminopropyltriethoxysilane, 3 Aminopropyltrimethoxysilane, separately. Sol-gel methodology is the best alternative protocol to synthesize mesoporous nanoparticles as the classic ways to obtain silica from natural sources are unable to produce silica with high purity and uniform size distribution. Amino functionalized silica nanoparticles were then grafted with Furfural as well as Coumarin derivatives to produce organic/inorganic hybrid materials. Furfural and its derivatives find applications in cosmetic, color and paint industries. To synthesize furfural derivatives, Meerwein arylation of furfural at 5th position with o-nitroanilin, m-nitroanilin and p-nitroanilin was carried out separately which gave 5-arylfurfurals. These 5-aryl furfural derivatives are bright colored compounds in the visible light. Coumarin, especially Coumarin-3-carboxylic acid and coumarin-3- carboxylic acid ethyl ester find their applications in medicinal chemistry. Coumarin.